Prevalence and correlates of depression and anxiety in caregivers of children with attention-deficit/hyperactivity disorder during the fifth wave of COVID-19 and school closure in Hong Kong - Samson Chun Hung; Anson Kai Chun Chau; Janet Hiu-Ching Lei; Eric Tsz-Him Lai; Gabbie Hou-Sem Wong; Iris Ka-Yan Leung; Wing-Chung Chang; Chung Ho; Brian Man-Ho Leung; Wilfred Shone-Horn Wong; Joe Kwun-Nam Chan; Krystal Chi-Kei Lee; et al. (Annals of General Psychiatry)
Abstract Background Caregivers of children with attention-deficit/hyperactivity disorder (ADHD) are vulnerable to increased psychological distress during COVID-19. However, specific pandemic- and child-related factors contributing to their poor mental health have not been fully investigated. We aimed to comprehensively examine prevalence and correlates of depression and anxiety among caregivers of ADHD children in Hong-Kong during the peak of fifth pandemic wave with territory-wide school closure. Method One-hundred-ninety-nine caregivers of ADHD children were assessed with self-rated questionnaires between 29 March–14 April, 2022. Questionnaires encompassed socio-demographics, pre-existing physical/psychiatric morbidity, COVID-19 related factors, children’s ADHD and other psychiatric symptoms. Caregivers’ psychological distress was quantified by Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder Scale-7 (GAD-7). Caregivers who scored ≥ 10 in PHQ-9 and GAD-7 were classified as having probable depression and probable anxiety, respectively. Univariate and multivariate logistic regression analyses were conducted to identify correlates associated with caregivers’ probable depression and anxiety status. Results Forty-four (22.4%) and 33 (16.9%) caregivers had probable depression and anxiety, respectively. Multivariate regression analyses revealed that caregivers’ pre-existing mental disorder, greater COVID-19 stressor burden, and more severe emotional symptoms and insomnia of ADHD children were independently associated with both caregivers’ depression and anxiety status. Conclusion A significant proportion of caregivers of ADHD children experienced clinically-significant depressive and anxiety symptoms during the peak of fifth pandemic wave and school closure. Findings suggest that optimizing management of caregivers’ pre-existing mental health conditions, addressing emotional and sleep symptoms in ADHD children, and implementing strategies to alleviate pandemic-related stressors may reduce caregivers’ psychological distress.